2021
DOI: 10.1007/s10856-021-06539-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose an effective material in the treatment of chronic venous ulcers of the lower limbs

Abstract: Chronic venous ulcers (CVU) of the lower limbs (LL) are common and cause psychological changes and significant social impact, as they make the patient susceptible to pain, absence from work and social bonds. Some materials are suggested as dressings for the treatment of CVU, but they are expensive and are generally not available for use in public health services. To evaluate the efficacy of the treatment for lower limbs (LL) chronic venous ulcer (CVU) using bacterial cellulose (BC), gel and multi-perforated fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
(82 reference statements)
0
10
0
1
Order By: Relevance
“…has undergone comprehensive evaluation in toxicity tests, as described by Pinto et al [34], and safety studies conducted by Silva et al [24]. Clinical research led by Silva et al [26] confirmed not only the safety of the product but also its high capacity to promote wound healing in chronic venous ulcers in the lower extremities, showing significant reductions in wound area, improved healing rates, and positive patient outcomes when compared to standard dressings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…has undergone comprehensive evaluation in toxicity tests, as described by Pinto et al [34], and safety studies conducted by Silva et al [24]. Clinical research led by Silva et al [26] confirmed not only the safety of the product but also its high capacity to promote wound healing in chronic venous ulcers in the lower extremities, showing significant reductions in wound area, improved healing rates, and positive patient outcomes when compared to standard dressings.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of hydrogel is similar to the extract of an extracellular matrix and soft tissues, which presents a distinct three-dimensional conformation of nanofibrils and microfibrils that enables the adhesion of compounds due to the hydroxyl groups that make up its surface [19][20][21][22]. A hydrogel produced from sugar cane molasses has been tested in different medical and biomedical areas, showing promising results, including stability due to sugar polymerization, low toxicity, biocompatibility, and efficiency for tissue remodeling [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Silva et al [ 134 ], a randomized controlled clinical intervention study of venous ulcers of the lower limbs using bacterial cellulose in the form of a membrane, gel, and multiperforated film was performed. The experimental group (EG), with 20 patients, was treated with BC-based dressings, and the control group (CG), with 19 patients, was treated with dressings made of a cellulose acetate mesh impregnated with essential fatty acids (RAYON ® ).…”
Section: Bc For Wound Dressingmentioning
confidence: 99%
“…Rayon dressings are often used to treat chronic leg ulcers. When compared to rayon dressings for wound care, BC dressings have been shown (Silva et al, 2021) to be superior due to lower dressing change frequency, minimized direct contact with wounds, less risk of contamination and infection, greater patient autonomy and less dressing adhesion to bed (Silva et al, 2021).…”
Section: Examples Of Bc Dressings In Clinical Applications and In Viv...mentioning
confidence: 99%